Altered cardiovascular rhythmicity in children born small for gestational age - Wolfenstetter, Ann Maria; Pöschl, Johannes; Schaefer, Franz; Wühl, Elke (Hypertension, 2012)
Low birth weight is frequently associated with a disproportionately high incidence of cardiovascular disease, diabetes mellitus, and kidney disease in adulthood. Epidemiological studies have identified an inverse association between low birth weight or being small for gestational age and hypertension in adulthood. We hypothesized that children born with low birth weight might have altered circadian and ultradian cardiovascular rhythmicity independent of the prevailing blood pressure level. Twenty-four-hour ambulatory blood pressure and heart rate rhythmicity was prospectively evaluated by Fourier analysis in a cohort of healthy children born with low birth weight and compared with normative pediatric data. Seventy-five children born small for gestational age (mean age, 8.1±2.2 years) and 139 controls matched for age and sex were investigated. In addition to increased 24-hour, daytime, and especially nighttime blood pressure levels (P<0.05), children born small for gestational age exhibited blunted circadi...
Originally published: 25 Jun 2012
Gesehen am 08.10.2018